Clinical characteristics and outcome in patients with anti-AMPAR2 encephalitis: a case series and literature review - Wang, Congcong; Kong, Fanyu; Yu, Xianwen; Li, Yan; Yang, Meihe; Si, Zhihua; Liu, Rutao; Hu, Ke; Yang, Bing (Frontiers in Human Neuroscience, 2025)
Anti-alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor encephalitis is a rare autoimmune encephalitis, with only a few series describing its typical clinical manifestations and prognosis. Here, we present three newly identified patients with anti-AMPAR encephalitis and were followed up for prognostic evaluation. The mean age of the patients was 47 years (range, 32–57). All three patients experienced memory issues, with two showing signs of typical limbic encephalitis (LE). Cranial magnetic resonance imaging (MRI) in two patients demonstrated lesions in the bilateral temporal lobes, insula, and cingulate gyrus as well as significant cortical atrophy after 1 month of follow-up. No acute lesions were observed on cranial MRI in the third patient at the onset of symptoms. One patient had positive antibodies for both AMPAR1 and AMPAR2 in cerebrospinal fluid (CSF), while the other two patients only had positive antibodies for AMPAR2. Severe clinical symptoms and high CSF antibody levels were found in two patients. Immunotherapy demonstrated partial efficacy in all three patients. Two patients exhibited favorable responses to first-line immunotherapy. In contrast, the third patient experienced a suboptimal response to the initial treatment, with no remission and subsequent disease relapse. Following second-line immunotherapy, her condition stabilized; however, she continued to suffer from significant cognitive impairment. One patient was diagnosed with a viral infection, but no tumors were found in any patients. Besides its typical manifestation as LE, anti-AMPAR2 encephalitis may also present as simple amnesia. It is advised to monitor CSF antibodies and their level changes. While first-line immunotherapy is partially effective, some patients may need additional second-line therapy. Viral infections could be a predisposing factor; thus, routine CSF virus testing is recommended. Additionally, screening for tumors and follow-up assessments are also important.